If you were born a kitten - Bauer, Marion Dane.; McAllister Stammen, Jo Ellen (New York : Simon & Schuster Books for Young Readers, 1997)
Simply describes how various baby animals come into the world and what happens when a human baby is born.
Keywords: Animals; Animals; Birth; Babies